1982
DOI: 10.1017/s0016756800026066
|View full text |Cite
|
Sign up to set email alerts
|

Chlorite-mica stacks in low-strain rocks from central Wales

Abstract: Weakly deformed, low grade, Lower Palaeozoic metasediments from central Wales contain abundant stack-like intergrowths of chlorite and white mica that closely resemble stacks described from the Devonian Hunsruckschiefer of West Germany; the Ordovician Martinsburg Slate, New Jersey, U.S.A.; and elsewhere. Several theories have been proposed to explain the origin of such stacks, including a detrital origin; strain-controlled growth of chlorite on a detrital mica nucleus; and strain-controlled intergrowth during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
3

Year Published

1986
1986
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 17 publications
(18 reference statements)
7
39
3
Order By: Relevance
“…Also the transformation of illite into muscovite and the increasing iron content in chlorites have been related to increasing temperature-pressure conditions (e.g., White et al, 1985). The results of the present study and those of other authors (e.g., Craig et al, 1982;White et al, 1985) suggest that alteration of biotite during diagenesis is a potential source of K and/or (Fe + Mg) for the authigenesis of illites and chlorites.…”
Section: Discussionsupporting
confidence: 72%
“…Also the transformation of illite into muscovite and the increasing iron content in chlorites have been related to increasing temperature-pressure conditions (e.g., White et al, 1985). The results of the present study and those of other authors (e.g., Craig et al, 1982;White et al, 1985) suggest that alteration of biotite during diagenesis is a potential source of K and/or (Fe + Mg) for the authigenesis of illites and chlorites.…”
Section: Discussionsupporting
confidence: 72%
“…Grains with a modified detrital outline and consisting of subparallel packets of chlorite and white mica, referred to as chlorite-mica stacks, range from 10-I 50 /zm in size and are dispersed throughout the matrix, along with occasional quartz and albite clasts. The occurrence and origin of the chlorite-mica stacks have been studied by many workers (e.g., Craig et al, 1982;Woodland, 1985;Dimberline, 1986;Milodowski and Zalasiewicz, 1991;Li et al, 1992b). Li et al (1994) concluded that they were largely detrital biotite grains, subsequently modified during the progression from diagenesis to low-grade metamorphism.…”
Section: Specimenmentioning
confidence: 99%
“…In clastic sedimentary rocks, phyllosilicate stacks consisting ofinterstratified parallel or subparallel packets of two different phyllosilicate phases have been shown to originate from detrital phyllosilicate grains, with or without recrystallization, in response to diagenetic/metamorphic conditions (e.g., Roy, 1978, Craig et al, 1982van der Pluijm and Kaars-Sijpesteijn, 1984;Gregg, 1985;Woodland, 1985;Dimberline, 1986;Morad, 1986). Deformation features due to tectonic stress are commonly observed in such stacks.…”
Section: Alteration Of Chlorite To Berthierinementioning
confidence: 99%